PEMIKIRAN ILMU FALAK KYAI NOOR AHMAD SS - J., Jayusman (Ahkam: Jurnal Hukum Islam, 2017)
Kyai Noor Ahmad SS was a profound ahli falak (astronomer) in the Nahdhatul Ulama (NU) organization. His contribution in the field of astronomy led him to be a member of the authors in the almanac of the committee of NU. He also contributed to the decision of any policy made by Lajnah Falakiah NU, an institution which concerns with astronomy. His masterpiece, Nur al Anwar, is used as a reference by the Ministry of Religious Affairs in deciding the first and the last day of Ramadhan and the first day of Zulhijjah. The thought of astronomers come up with more or less similar method but kyai Noor’s thought is interesting to investigated further due to his great experience in working with astronomy. Kata kunci: Noor Ahmad SS, Awal Waktu Salat, Arah Kiblat, Awal Bulan Kamariah, Gerhana